PERJANJIAN PEMBERIAN KUASA PENJUALAN BARANG DENGAN SISTEM COUNTER PADA PERTOKOAN BIG MALL SAMARINDA - Ria Pratiwi (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
AbstrackContracts for the sale of goods with the power of counter system, originally done by agreement between the parties. Suppleir first party to apply the clause care goods to the Big Mall, followed by bidding on all terms of the agreement referred to by the Big Mall. After suppleir approve all the requirements of the suppleir gave agree on terms perjanijian indicated, these agreements can be realized that the form of the delivery of goods by suppleir the Big Mall. A series of legal actions that legally can be qualified as an act of authorization of suppleir. In deed the agreement, as exemplified in section I of Chapter III, Article 12 determined that determine all matters relating to the power sales contracts for goods in question, either on a counter salesperson, sales system. responsibilities of the parties, penalties in the event of a dispute because of non-fulfillment of achievement, payment procedures, the expiration of the agreement.